Early Percutaneous Dilatational Tracheostomy to Facilitate Ventilator Weaning in a Patient with Blunt Abdominal Trauma and Hemorrhagic Shock: A Case Report - Putra, Adrian Nugraha (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Hemorrhagic shock and the requirement for continuous mechanical breathing are frequent outcomes of blunt abdominal injuries, a dangerous illness. Long-term endotracheal intubation increases the risk of ventilator-related problems. In critically ill patients, percutaneous dilatational tracheostomy (PDT) has been proposed as a means of facilitating their transition off the ventilator and reducing the risk of pulmonary complications.Case: A 53-year-old woman showed up after falling from around 10 meters in the air. It was discovered that she had suffered blunt abdominal trauma, which caused hemorrhagic shock and extensive brain bruises. An exploratory laparotomy was done in an emergency. This treatment included fixing a left kidney tear, restoring the bladder, and establishing a transverse colostomy because of colon damage. She needed continuous mechanical ventilation in the intensive care unit after surgery. On the seventh day of intubation, an early percutaneous dilatational tracheostomy (PDT) was performed because the patient was having trouble detaching from the ventilator. Fifteen days after the PDT was implanted, the patient's respiratory state gradually improved, and she was successfully decannulated. She spent 23 days in the hospital overall.Discussion: In trauma patients who need continuous mechanical ventilation, tracheostomy may result in improved comfort, less sedation, simpler pulmonary toileting, and perhaps a decrease in ventilator-associated pneumonia. In this instance, successful ventilator weaning without major complications was made possible by early PDT performance.Conclusion: Early percutaneous dilatational tracheostomy is a safe and efficient way to help trauma patients who have been on mechanical breathing for a long time wean themselves off of it. For best results, time and patient selection are crucial. Keywords:ventilator weaning, hemorrhagic shock, percutaneous dilatational tracheostomy, and blunt abdominal trauma